SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/95571-ms
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of Variable-Rate Reservoir Performance Data Using B-Splines

Abstract: This work presents the development, validation and application of a novel deconvolution method based on B-splines for analyzing variable-rate reservoir performance data. Variable-rate deconvolution is a mathematically unstable problem which has been under investigation by many researchers over the last 35 years. While many deconvolution methods have been developed, few of these methods perform well in practice -and the importance of variable-rate deconvolution is increasing due to applications of permanent dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…for a given rate function, ( ) t q (Ilk et al, 2005). In deconvolution, this causes small errors in data, especially in ( ) t q , to yield large variations (errors) in the deconvolved constant-rate response.…”
Section: Convolution and Deconvolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…for a given rate function, ( ) t q (Ilk et al, 2005). In deconvolution, this causes small errors in data, especially in ( ) t q , to yield large variations (errors) in the deconvolved constant-rate response.…”
Section: Convolution and Deconvolutionmentioning
confidence: 99%
“…In other words, it is possible to improve the success of a given deconvolution algorithms by improving the numerical inversion of Laplace transforms of discontinuous or piecewise differentiable functions. Along these lines, Ilk et al (2005) have noted the importance of the numerical inversion algorithm used to invert the Laplace transform of the sampled rate function in their deconvolution approach using B-splines. Our renewed interest in the problem was driven by a new algorithm presented by Iseger (2006) that claims to handle singularities and discontinuities.…”
mentioning
confidence: 99%
“…Based on this method, Levitan (2005) and Levitan et al (2006) made some improvements with practical considerations. Ilk et al (2006) presented B-spline deconvolution and applied this algorithm on the gas well test. With the installation of permanent down-hole pressure and flow-rate measure systems, deconvolution becomes more important because it can process pressure and rate data simultaneously and can obtain the underlying reservoir properties, which change with time (Onur et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Levitan (2005) and Houze et al (2010) demonstrated that deconvolution fails for the changes of the wellbore storage and skin case. Ilk et al (2010) discussed several scenarios where deconvolution is invalid, such as gas flow, multiphase flow, and non-Darcy flow. These nonlinearities usually are caused by the changes in reservoir properties and well conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation